(3eLehY aj GdcjejGAs - (3LGHQ Hf MjGf Hf YHO Gddg Gdchaj, CHh ehSi, J (B200 (3g` s
(3ChdgG (B:s
(3hHYO abO hVYJ cJGHi gPG hSejJg cJGH TQM GSJbUi GdCS afbhd hHGddg GdJhajb Cf GdYbhd gi COGJfG GdJi HgG jecf ef Yde GdehLhOGJ LejYgG s
(3BNQgG (B:s
(3aGMaX gPg GdTQGFW hGQLY ai Pdc Edi HbjI GdcJH aEfc JLO Pdc eSWhQkG hGVMkG eTQhMkG aGYed Hg Je cJGH TQM cJGH GdQMeI GdeYfhf HcJGH GdCS s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3HgG CKGQ WeSs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B103s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1419s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdcjejGA h GdWHjYjGJs